Aktivitas Antioksidan Ekstrak Etanol Daun Jarak Pagar (Jatropha curcas L.) Melalui Metode FRAP dan Penambatan Molekuler - Sadik, Fahmi; Marwati, Eri (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2024)
This study evaluated the antioxidant activity of Jatropha curcas L. leaf ethanol extract via Ferric Reducing Antioxidant Power (FRAP) assay and molecular docking against Superoxide Dismutase 1 (SOD1) enzyme. Extraction was performed by maceration using 96% ethanol. In vitro results showed the extract possessed moderate antioxidant capacity of 3.52 mg TE/g and contained flavonoids and tannins. In silico analysis revealed that Naringenin-7-O-β-D-glucopyranoside exhibited the highest binding affinity towards SOD1 with a Gibbs free energy of -10.41 kcal/mol, surpassing the co-crystal ligand (-9.05 kcal/mol). Stable interactions were formed through hydrogen bonds at key residues LYS175 and TRP109. This study concludes that J. curcas leaves have dual potential as electron donors and modulators of body defense enzymes for combating oxidative stress.